2016
DOI: 10.1098/rstb.2015.0188
|View full text |Cite
|
Sign up to set email alerts
|

Feeding innovations in a nested phylogeny of Neotropical passerines

Abstract: One contribution of 15 to a theme issue 'Innovation in animals and humans: understanding the origins and development of novel and creative behaviour'. Several studies on cognition, molecular phylogenetics and taxonomic diversity independently suggest that Darwin's finches are part of a larger clade of speciose, flexible birds, the family Thraupidae, a member of the New World nine-primaried oscine superfamily Emberizoidea. Here, we first present a new, previously unpublished, dataset of feeding innovations cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 43 publications
2
43
2
Order By: Relevance
“…Tebbich et al suggested that Darwin's finches might exemplify this pattern [40], and Lefebvre and colleagues reasoned that if that were right, the clade which contains Darwin's finches should show high rates of innovation, and members of the clade on other islands should likewise show high levels of individual adaptability. They confirmed both predictions [25]. A macroevolutionary pattern-adaptive radiation and high rates of populationlevel innovation-is explained by the characteristics of individual agents.…”
Section: Missing Linkssupporting
confidence: 75%
See 1 more Smart Citation
“…Tebbich et al suggested that Darwin's finches might exemplify this pattern [40], and Lefebvre and colleagues reasoned that if that were right, the clade which contains Darwin's finches should show high rates of innovation, and members of the clade on other islands should likewise show high levels of individual adaptability. They confirmed both predictions [25]. A macroevolutionary pattern-adaptive radiation and high rates of populationlevel innovation-is explained by the characteristics of individual agents.…”
Section: Missing Linkssupporting
confidence: 75%
“…Likewise, Lefebvre et al recognize the role of predation threat in their choice of experimental models, choosing broad-niched island species, on the grounds that reduced predator threat makes these species more likely to innovate [25]. However, while a number of the papers in this volume discuss rates of innovation within different clades, and broad correlations between rates of innovation and morphological features (for example potential correlations between rates of technical innovation and brain size, see Navarrete et al [26]), and there is some discussion of whether innovation rates depend on ecological factors (in particular, on harsh environments) there is much less discussion of the relations between rates of innovation and broad geographical variables; for example, comparisons of island versus mainland species, or the relation between innovation rates and narrow versus broad geographical distribution.…”
Section: Environment and Innovationmentioning
confidence: 99%
“…2b in Lefebvre et al [91]). This is despite the Coeribinae showing high phenotypic variation in morphology and high diversification rates [93].…”
Section: Innovation and The Flexible Stem Hypothesismentioning
confidence: 99%
“…Dietary specialization would predict that Darwin's finches should have lower levels of innovations than would be expected relative to research effort. Clearly, more study is needed in the closely related, apparently highly innovative Thraupinae [91]. One should also bear in mind that the conclusions of comparative analyses, especially those that drill down to low taxonomic levels, are vulnerable to changes in phylogenetic classifications and yield very small numbers of innovations, reducing the power to identify patterns.…”
Section: Innovation and The Flexible Stem Hypothesismentioning
confidence: 99%
See 1 more Smart Citation